TINDAK TUTUR PROGRAM PODCAST WARUNG KOPI DALAM CHANNEL YOUTUBE HAS CREATIVE: KAJIAN PRAGMATIK - Sinta Nurliya; Achmad Wahidy; Yenny Puspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the types of speech acts and their influence in building interactions between speakers and speech partners. This can certainly take place well and run smoothly because there is a principle of cooperation put forward by Grice, namely four maxims, namely quantity, quality, relevance, and methods that must be adhered to in communication on the HAS Creative Youtube Channel Coffee Shop Podcast Program. The type of research used is qualitative research with a descriptive method. The data source in this study comes from the HAS Creative Youtube Channel Coffee Shop Podcast Program. The data in this study are all speech acts of oral sources in communication activities which are classified into locutionary speech acts, illocutionary speech acts, and perlocutionary speech acts. By using the principle of cooperation that proposes four maxims, namely quantity, quality, relevance, and manner that must be adhered to by participants in the conversation so that communication runs effectively in the interaction between the host and the resource person. The data collection technique used is the listening and note-taking technique. Based on the results of the speech act research conducted, thirty-one data were found consisting of eight locutionary speech sentences, eleven illocutionary speech sentences, twelve perlocutionary speech sentences. In addition, it was also found from the research on the principle of cooperation maxims that were conducted, there were thirty-one data consisting of eight quantity maxim speech sentences, fifteen quality maxim speech sentences, seven relevance maxim speech sentences, and one maxim speech sentence data.